KRIMINALISASI TERHADAP PERILAKU PENYIMPANGAN SEKSUAL - welly Kendra (UNES Journal of Swara Justisia, 2020)
Kota Pariaman has enacted Regional Regulation Number 10 of 2018 which stipulates a policy of criminalization for sexual deviant behavior by LGBT. Forms of Criminalization of Sexual Abuse Behavior in the Regional Regulation of Pariaman City Number 10 Year 2018 is against behavior that is prohibited from being based on moral background. To maintain public morality, in the criminalization of LGBT, the City of Pariaman government imposes sanctions in the form of administration, which is the cost of enforcing local regulations and in the form of penalties in the form of fines and confinement in the alternative criminal system. Comparison of arrangements in Pariaman City Regulation No. 10 of 2018 explained in detail about the understanding of transgender and LGBT. The Criminal Code Bill does not provide a more detailed explanation, it only provides a regulation on what is meant by "obscenity".